Characterization of The Heat Transfer in Film Boiling with Spray Quenching for Different Material Properties - Sabariman, Sabariman (Telcomatics, 2017)
A hot aluminum alloy AA6082 and nickel disc of 560 Â°C and 850 Â°C was cooled by a spray nozzle with the spray flux of 4.2, 10 and 13.7 kg/m2s. The temperature history during the cooling process was recorded with use of an infrared camera. The energy balance equation is the basis for the numerical procedure of Heat Transfer Coefficient (HTC) calculation in the film-boiling regime. It is found that HTC is almost independent from kind of metals. HTC has a stronger function of surface temperature. With use of single droplet model in film boiling developed, vapor film thickness can be calculated to predict this trend.